2021
DOI: 10.1186/s12885-021-08824-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and treatment profiles of patients with concurrent Epidermal Growth Factor Receptor (EGFR) and Anaplastic Lymphoma Kinase (ALK) mutations

Abstract: Background EGFR and ALK alternations often contribute to human malignancies, including lung cancer. EGFR and ALK mutations are usually sensitive to EGFR-tyrosine kinase inhibitors (TKIs) and ALK-TKIs. Although generally mutually exclusive, these mutations do co-exist in rare cases. This study investigated the frequencies, clinical characteristics, therapeutic efficacies, and genetic profiles of lung cancer patients with EGFR and ALK co-mutations. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(29 reference statements)
0
1
1
Order By: Relevance
“…[34][35][36] Therefore, we concluded that the incidence of oncogenic driver genes detected in MPE was similar to that in tumor tissues. The EGFR and ALK co-mutation incidence in our study was 3.3% (2/61), which was higher than that in tumor tissue (<1%), 37 possibly because the tumor cells in the MPE may come from all sites of the tumor. In this respect, MPE specimens could overcome the limitation of tumor heterogeneity and, as mentioned above, this may account for the higher incidence of EGFR T790M mutations.…”
Section: Progression-free Survival and Overall Survivalcontrasting
confidence: 63%
“…[34][35][36] Therefore, we concluded that the incidence of oncogenic driver genes detected in MPE was similar to that in tumor tissues. The EGFR and ALK co-mutation incidence in our study was 3.3% (2/61), which was higher than that in tumor tissue (<1%), 37 possibly because the tumor cells in the MPE may come from all sites of the tumor. In this respect, MPE specimens could overcome the limitation of tumor heterogeneity and, as mentioned above, this may account for the higher incidence of EGFR T790M mutations.…”
Section: Progression-free Survival and Overall Survivalcontrasting
confidence: 63%
“…In addition, Mohapatra et al [ 19 ] pointed out that, owing to economic stress, clinicians in developing countries preferred to choose EGFR-TKIs as the first-line targeted drugs for NSCLC patients with co-mutations of EGFR and ALK genes. Moreover, Yang et al [ 20 ]reports for the first time that EGFR-TKIs-treated patients with EGFR/ALK-L1152R mutations generally had a shorter PFS than patients with other mutation combinations(the mPFS of 4 mo vs 18.2 mo, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%